2020
DOI: 10.31616/asj.2019.0025
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Improved Intraoperative Neurophysiological Monitoring Signal during Spine Surgery: A Retrospective Study of a Single-Institution Prospective Cohort

Abstract: Study Design: Retrospective case series. Purpose: We reviewed the cases that showed significant improvement of intraoperative neurophysiological monitoring (IONM) signals during spine surgery to assess whether there is a correlation with signal improvement and postoperative clinical status and its clinical significance. Overview of Literature: To reduce the risk of neural injury, many spine surgeons are using multimodality IONM. Although many studies attempted to identify valid alarm criteria for predicting po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
0
11
0
4
Order By: Relevance
“…However, specifying these predictions with actual numerical values and parameters that have been validated has another important meaning. Numerous studies have been conducted on several factors related to the surgical outcome [30][31][32]. These are the demographic data of the patients before surgery, radiologic parameters of the patients undergoing surgery, and factors related to surgery such as operation time and intraoperative blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…However, specifying these predictions with actual numerical values and parameters that have been validated has another important meaning. Numerous studies have been conducted on several factors related to the surgical outcome [30][31][32]. These are the demographic data of the patients before surgery, radiologic parameters of the patients undergoing surgery, and factors related to surgery such as operation time and intraoperative blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…Another study was made by Wi et al [ 14 ] on 29 improved IONM of spine cases compared to the baselines out of 317 cases with IONM of spine cases and their clinical significance. The surgeries' IONM data were chosen between January 2013 and May 2017.…”
Section: The Significance Of Mep Improvementmentioning
confidence: 99%
“…There are a few reports that MEP amplitude significantly increased after spinal cord decompression. [ 8 , 9 , 15 ]. In these studies, MEP amplitude was related to clinical outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, only two previous studies have focused on neurological improvement or surgical decompression of the spinal cord. In those studies, intraoperative MEP amplitude significantly improved during surgical decompression, and Wang et al found a cut-off value of 150%, and Wi et al found a cut-off value of 200% [ 8 , 9 ]. Our result is similar to those, but further data are needed to determine the cut-off point.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation